PEMETAAN SOSIAL DAN PARTISIPASI STAKEHOLDER DALAM PERENCANAAN PROGRAM PENGEMBANGAN EKONOMI KOMUNITAS DI DESA MAPILA KECAMATAN KABAENA UTARA KABUPATEN BOMBANA - Muhammad Aldin; Iskandar Zainudin Rela; Budiyanto Budiyanto (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This study aims to conduct socio-economic mapping of the community in Mapila Village, North Kabaena Sub-district, taking into account stakeholder perceptions as a basis for community economic development planning. The study used a qualitative descriptive method focusing on socio-economic conditions and stakeholders' perceptions, using Rapid Rural Appraisal (RRA) techniques, household surveys, Focus Group Discussions (FGDs), and semi-structured interviews. The research findings reveal important insights into the community's socio-economic conditions, stakeholder perceptions, and proposed development programmes, and emphasise the importance of collaboration between the government, private sector, and community in creating effective and sustainable development strategies. The research highlights the need to improve education facilities, health services, infrastructure and economic empowerment programmes to support sustainable development in Mapila Village.